2015
DOI: 10.1177/230949901502300232
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic Nerve Schwannoma: A Case Report

Abstract: We report on a 46-year-old woman with a sciatic nerve schwannoma. Magnetic resonance imaging revealed a well-defined, lobulated, intensely enhancing mass posterior to the left hip joint along the left sciatic nerve suggestive of neurogenic tumour. The Tinnel sign was positive on the posterior aspect of the left thigh. The tumour was excised without neural damage. Postoperatively, the patient showed no signs of any neurological deficit, and recovery was uneventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The radicular type of leg pain is typically attributed to a degenerative spinal pathology, hence even in the presence of typical pain, diagnosing a schwannoma is often delayed. Therefore, a whole limb imaging study, preferably an MRI scan recommended for patients, who are having the characteristic symptoms of neural pathology while the preliminary investigation findings rule out any degenerative spinal pathology (5,6). Nevertheless, in our case, the benign peripheral nerve sheath tumour (PNST) was incidentally diagnosed during a vascular doppler study.…”
Section: Discussionmentioning
confidence: 80%
“…The radicular type of leg pain is typically attributed to a degenerative spinal pathology, hence even in the presence of typical pain, diagnosing a schwannoma is often delayed. Therefore, a whole limb imaging study, preferably an MRI scan recommended for patients, who are having the characteristic symptoms of neural pathology while the preliminary investigation findings rule out any degenerative spinal pathology (5,6). Nevertheless, in our case, the benign peripheral nerve sheath tumour (PNST) was incidentally diagnosed during a vascular doppler study.…”
Section: Discussionmentioning
confidence: 80%
“…It often induces symptoms of radicular pain, and sensory or motor disturbances [12]. When involving the sciatic nerve, it can be asymptomatic or may present with sciatica or neurological deficits [13].…”
Section: Discussionmentioning
confidence: 99%
“…On rare occasions, a sciatic nerve tumour can also cause similar clinical manifestations. Filler et al reported that among patients with sciatica of non-disc origin, the incidence rate of pain caused by sciatic nerve tumours was 1.7% [ 16 , 17 ]. As previously reported in the literature [ 4 6 , 10 , 11 ], the reason for misdiagnosis as LDH is the lack of mastering of the exact physical examination method and an overdependence on the radiological examination.…”
Section: Discussionmentioning
confidence: 99%